PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION UNTUK MENINGKATKAN KETERAMPILAN METAKOGNITIF SISWA KELASVII SMP NEGERI 4 LAMBOYA - Agustinus Jawu Kalaga; Deny Setiawan (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2017)
Based on interviews and observations, the metacognitive skills of the seventh grade students of SMP Negeri 4 Lamboya are still low. This is because the thinking skills have not been empowered in school. Need effort to overcome this, one way that is implementation of learning model study of Group Investigation (GI). The purpose of applying the Group Investigation learning model (GI) to improve students' metacognitive skills. This research is a class action research (PTK) consisting of 4 stages of Planning, Action, Observation, Reflection which is implemented in two cycles. The subjects of the study were students of class VII A SMP Negeri 4 Lamboya academic year 2016/2017 as many as 23 students. The results showed that the percentage of masakognitif skill resulted from (51.08) in cycle I to (73,52) in cycle II. The conclusion of this research is Group Investigationstudy model (GI) can improve metacognitive skill of class VII A student of SMP Negeri 4 Lamboya.